From Legacy Threats to Modern Risks – Building a Cybersecurity Framework for Sporting Events - Nambissan, Priyanka (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
The increase of digital technologies and raising connexion of operational infrastructures within sporting events have rendered cybersecurity a paramount concern. As the landscape of sporting events continues to evolve, so too does the imperative for robust cybersecurity measures. With the integration of technology into various facets of sporting activities—including ticket sales, complex digital supply chains, and interconnected infrastructures - the risk of cyber threats to athletes, fans, and organizations has escalated. This paper provides a comprehensive review of existing cybersecurity frameworks applicable to sporting events, while emphasizing the challenges posed by emerging threats. We discuss the necessity for continuous review, adaptation, and integration of advanced technologies such as threat intelligence, dynamic monitoring, and resilience engineering to counter evolving cyber risks. In doing so, we synthesize research findings from multiple studies that highlight the dynamic nature of cyber threats and propose adaptive solutions critical for safeguarding sporting events and propose a robust framework tailored for enhancing security in this unique sector.